Pengaruh Penggunaan Alat Peraga Papan Berpasangan pada Materi Operasi Bilangan Bulat terhadap Hasil Belajar Matematika Peserta Didik - Muhammad Risman; A. Sriyanti; Munirah; Thamrin Tayeb; Lisa Kurnia Syam (Al Asma: Journal of Islamic Education, 2023)
Understanding the concept of abstract arithmetic operations requires visual aids such as concrete objects that can provide visualization to students. This study aims to determine the effect of using paired board teaching aids on integer operations material on students' mathematics learning outcomes. The research method used is quantitative with the type of pre-experimental research design and the research design is one-group pretest-posttest design. The population of this study were all fifth grade students at SDN 103 Kalimporo, totaling 32 students. The sampling technique used is saturated sampling technique so that the sample in this research is class V. The instruments used are pretest and posttest. The data analysis technique used is descriptive and inferential statistical analysis. Based on the results of the analysis using simple regression analysis and t-test, the regression equation is obtained. With the t-test value, the value is , thus it can be concluded that there is an effect of using paired board teaching aids on integer operations material on the learning outcomes of class V students at SDN 103 Kalimporo.